Bone metabolism parameters and inactive matrix Gla protein in patients with obstructive sleep apnea†. Issue 3 (21st October 2019) - Vilovic, Marino; Dogas, Zoran; Ticinovic Kurir, Tina; Borovac, Josip A; Supe-Domic, Daniela; Vilovic, Tina; Ivkovic, Natalija; Rusic, Doris; Novak, Anela; Bozic, Josko
Abstract: Study Objectives: The aim of this study was to investigate differences in dual-energy X-ray absorptiometry (DXA) parameters, trabecular bone score (TBS), bone turnover markers and inactive matrix Gla protein (dp-ucMGP) between patients with obstructive sleep apnea (OSA) and healthy controls. Methods: This study enrolled 53 male patients diagnosed with OSA, and 50 age- and body mass index (BMI)-matched control subjects. All participants underwent DXA imaging, TBS assessment and blood sampling for biochemical analysis of bone metabolism markers. Results: Mean apnea–hypopnea index (AHI) score of OSA patients was 43.8 ± 18.8 events/h. OSA patients had significantly higher plasma dp-ucMGP levels in comparison to controls (512.7 ± 71.9 vs. 465.8 ± 50.9 pmol/L, p < 0.001). OSA and control group did not significantly differ regarding standard DXA results, while TBS values were significantly lower in the OSA group (1.24 ± 0.17 vs. 1.36 ± 0.15, p < 0.001). AHI score was a significant independent correlate of plasma dp-ucMGP levels (β ± SE, 1.461 ± 0.45, p = 0.002). In addition, TBS retained a significant relationship with dp-ucMGP values (β ± SE, −93.77 ± 38.1, p = 0.001). Conclusions: dp-ucMGP levels are significantly higher in patients with OSA and correlate with disease severity. In addition, TBS values in OSA patients are lower in comparison with the control group and decrease with disease severity.